Experimental upper bound on phosphate radical production in TiO2 photocatalytic transformations in the presence of phosphate ions - Brusa, Marta Adelina (2003)
The spin trapping technique using 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) was used to investigate the involvement of phosphate radicals in TiO2-photocatalyzed systems. A persistent (HO)2PO2–DMPO˙ adduct (aN = 14.6 G, aHβ = 12.4 G, aHγ = 1.1 G and aP = 0.5 G) was first synthesized by UV photolysis of aqueous peroxodiphosphate solutions, at pH 4.0, in the presence of DMPO. The trapping efficiency of the phosphate radicals, η, determined at [DMPO] = 0.3 mM was η = 35%. In the heterogeneous system, the rate of HO–DMPO˙ aminoxyl radical generation under continuous UV irradiation of TiO2 sols, at [DMPO] = 0.3 mM and pH = 4.0, becomes gradually inhibited increasing [(HO)2PO2−] above 0.1 mM. However, no evidence of (HO)2PO2–DMPO˙ could be obtained in the whole range of conditions explored in this work (0.1 ≤ [DMPO]/mM ≤ 1 mM, 0.1 ≤ [(HO)2PO2−]/mM ≤ 100 mM). Based on the above experiments, we estimated a conservative upper limit for the quantum yield of (HO)2PO2˙ production, Φ = 2.0 × 10−4, in phosphate loaded TiO2 particles. The analysis of this result and its implications for the mechanism of the TiO2 photocatalytic oxidations of organic compounds in the presence of phosphate are discussed.